METODE BERMAIN UNTUK MENGEMBANGKAN KECERDASAN ANAK USIA DINI: Methods Of Play, Development, Intelligence Early Childhood - Made Ayu Anggreni (Buana Pendidikan, 2014)
Study about the method of play to develop early childhood intelligence. In the writing of this article used a descriptive method through the study of librarianship. Methods play an important role in the development of children in the field of motor-physical development, language, cognitive, social-emotional, moral. Through the method of play can improve the quality of education, because that method is more emphasis on the involvement of children directly by providing experiences in learning through play so as to make active and creative children in learning, then the development of intelligence of child or students can develop optimally. Knowledge about the play as well as to the development of children's intelligence and keep in mind by teachers, parents and education experts. So that in the process of early childhood education can run well. Teachers in implementing the method and preparing learning materials tailored to the interests and stages of child development. The teacher as a facilitator should be creative to create a wide variety of games and variations of the main tools, either from the former or invites the modern plays and traditional.